76.4k views
2 votes
Please help me solve this and please explain too thank you

2 {x}^(2) + 5x - 12 = 0

User Muny
by
5.6k points

2 Answers

5 votes

That is a quadratic equation in which:

a = 2 b = 5 and c=-12

We use the quadratic formula:

x = (-b +- sqr root (b^2 - 4*a*c)) / 2*a

x = (-5 +- sqr root (25 - 4 * 2 * -12)) / 2 *2

x = (-5 +- sqr root (25 +96)) / 4

x = (-5 +- 11) / 4

x1 = 6 / 4 = 1.5

x2 = -16 / 4 = -4


3 votes

2x^2 + 5x - 12 = 0

2x^2 + 8x - 3x - 12 = 0

2x(x + 4) - 3(x + 4) = 0

(2x - 3)(x + 4) = 0

2x - 3 = 0 or x + 4 = 0, so:-

solution is 3/2, -4.

User Pavan Bilagi
by
4.6k points